Taking advantage of a historic opportunity? A critical review of the literature on TOD in China - Jean-François Doulet; Aurélien Delpirou; Teddy Delaunay (Journal of Transport and Land Use)
Since the term was coined in the United States in the early 1990s, the concept of transit-oriented development (TOD) has enjoyed worldwide success. For emerging countries that are both experiencing fast urban growth and involved in the development of mass transit transportation networks, innovative planning practices are needed. Researchers have identified the recent development of subway networks in Chinese cities as an opportunity to implement TOD principles. Based on an extensive literature review, including Chinese sources, this paper aims to identify the way in which the concept of TOD has led to the emergence of a challenging research field dedicated to the integration of urban and transportation planning in China. Results from grounded studies have failed to prove that Chinese cities are "real" TOD cities in the formal sense; however, they are useful for identifying the key factors behind the lack of integration between transportation and urban development that are likely to influence planning, design, and research practice in China in the future.